Peran Orang Tua dalam Motivasi Belajar Peserta Didik Paket B Kelas VIII SKB Gudo Jombang - Suryatiaraszahri, Adhelia; Widodo, Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research is aimed to examine and analyze the role of parents in the learning motivation of Package B (National Junior High School Equivalency) in SKB Class VIII SKB (District Technical Office for Early Childhood, Nonformal and Informal Education) Gudo Jombang students. The method used was a descriptive qualitative method with research subjects of 9 informants. Data collection techniques were carried out using in-depth interviews, participant observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions. The results of the research show that each parent has their own way of providing learning motivation to students, including 1) motivation in the form of words 2) motivation in the form of action 3) motivation in the form of a gift. Students have varying levels of learning motivation with several aspects that need to be considered, including those related to 1) persistence in doing assignments, 2) tenacity in facing difficulties, 3) interest in learning, 4) liking to work independently, 5) quickly getting bored with assignments. repetitive, 6) can defend opinions, 7) does not easily give up things he believes in, and 8) enjoys finding and solving problems.